Can film be used to communicate the value and importance of subsistence hunting for Inuit in the Canadian Arctic to non-Indigenous populations? - Schindler, R; Pearce, T (ArcticNet Inc., 2013)
This poster describes research that examines how film may be used to communicate the value and importance of subsistence hunting for Inuit to non-Indigenous populations in a case study of seal hunting among Inuit in Ulukhaktok, Northwest Territories, Canada. Subsistence hunting is the basis for food production among Inuit and has strong economic, dietary and cultural importance. The value and importance of subsistence hunting for Inuit, however, is sometimes not reflected in the decisions of non-Indigenous populations such as the ban on the importation of seal products to several countries with negative impacts for Inuit communities. Th e objectives of the research are to use film to: (1) document and explain the value and mportance of subsistence seal hunting for Inuit; (2) portray subsistence seal hunting through the eyes of Inuit hunters and their families; and (3) preserve and promote the value and importance of subsistence seal hunting to younger generation Inuit and non-Indigenous populations. A short documentarystyle film will be created in partnership with Inuit in the hamlet of Ulukhaktok. Th is will involve conducting filmed interviews with community members about the importance of seal to their diet and culture and through participant observation and filming of seal hunting, fur and meat preparation, food sharing, and sewing. Th e project responds to the anti-sealing protests of some non-Indigenous peoples and seeks to communicate an honest and accurate presentation of the value and importance of seal hunting for Inuit. Th e research is part of the CIHR-funded IK-ADAPT (Inuit traditional knowledge for adaptation to the health eff ects of climate change) [www.ikadapt.ca] and the Health Canada funded project ‘Nunamin Illihakvia: Learning from the land.’